Chemogenetic modulation of the medial prefrontal cortex regulates resistance to acute stress-induced cognitive impairments. (24th September 2022) - Jeon, Yong-Jae; Park, Jung-Cheol; Jang, Yoon-Sun; Kim, Dong-Hee; Choi, Bo-Ryoung; Kim, Jae-Min; Kim, Jeansok J; Han, Jung-Soo
Abstract: The medial prefrontal cortex (mPFC) has been implicated in regulating resistance to the effects of acute uncontrollable stress. We previously showed that mPFC-lesioned animals exhibit impaired object recognition memory after acute exposure to a brief stress that had no effect in normal animals. Here, we used designer receptors exclusively activated by designer drugs to determine how modulating mPFC activity affects recognition-memory performance under stressful conditions. Specifically, animals with chemogenetic excitation or inhibition of the mPFC underwent either a brief ineffective stress (20-min restraint + 20 tail shocks) or a prolonged effective stress (60-min restraint + 60 tail shocks). Subsequent recognition memory tests showed that animals with chemogenetic mPFC inhibition exposed to brief stress showed impairment in an object recognition memory task, whereas those with chemogenetic mPFC excitation exposed to prolonged stress did not. Thus, the present findings the decreased mPFC activity exacerbates acute stress effects on memory function whereas increased mPFC activity counters these stress effects provide evidence that the mPFC bidirectionally modulates stress resistance.